Determination of Antioxidant Activity, Total Flavonoids and Carotenoids Content of Morning Glory (Impomoea aquatic Forsk) - BRIATIA, Xoxiong; SENGMANICHANH, Bounpeng; SALITXAY, Timnoy (Souphanouvong University Journal Multidisciplinary Research and Development, 2019)
This study aims to determine the antioxidant activity, total flavonoids and carotenoids content of Morning Glory species and to compare its compounds content of the stems, branch leaves, old leaves and young buds (epicotyls) parts. Red, Round shape leaves and Long shape leaves morning glory species were used for this study. Results found the species of Round shape leaves and Red species shown quantity of antioxidant activity, total flavonoids and carotenoids content higher than that Long shape leaves species. The highest content of antioxidant activity was at stems (91.42 and 90.05%), following by branch leaves (86.87 and 89.03%) and young bud (80.72 and 82.02%), and higher than at old leaves (77.87 and 76.22%) of Round shape leaves and Red species, respectively. While, Long shape leaves species showed highest in order such as old leaves > young bud > branch leaves > stems. Likewise, total flavonoids content was found highest at the older leaves (201.93, 232.84 and 128.36 mg/g) and young bud (199.70, 204.07 and 130.32 mg/g) which were higher than that at branch leaves (74.79, 118.63 and 29.79 mg/g) and stems (49.88, 79.96 and 41.13 mg/g) of the three species, respectively. On the other hand, total carotenoids content shown height in order such as old leaves (3.44 and 2.09 mg/g) > young bud (2.57 and 1.34 mg/g) > branch leaves (1.83 and 0.52 mg/g) > stems (1.09 and 0.28mg/g) of Red and Round shape leaves species, respectively. Whereas, Long shape leaves species content carotenoids highest in order such as at young buds (3.58 mg/g) > old leaves (1.70 mg/g) > branch leaves (0.75 mg/g) > stems (0.69 mg/g), respectively.